Karakterisasi Individu Wereng Hijau NEPHOTETTIX VIRESCENS Distant Penular Aktif Virus Tungro Padi - Supriyadi & Retno Wijayanti . (Universitas Lampung, 2010)
Characterization of active transmitter among population of the leafhopper, Nephotettix virescens Distant in relation to the transmission of the rice tungro virus. The objective of this research was to identify the characteristics of Nephotettix virescens as the active transmitter of the rice tungro virus. The specimens of N. virescens active transmitter were determined by differing in their ability to transmit the tungro virus to healthy plants. These specimens were used as samples to identify their morphological and molecular characters. Five external morphological characters, namely length of head to abdomen, hind femur, head, fore wing, and length of stylet were measured to determined their character. The protein banding patterns of the active transmitter were identified by protein separating technique on SDS-Page. Based on the morphological characters, especially the length of head to abdomen, hind femur, head, fore wing, and length of stylet, it showed that N. virescens active transmitter and non transmitter were similar. There were no specific morphological characters for N. virescens active transmitter. However, N. virescens active transmitter showed different protein banding pattern. Three distinct protein bands, estimated as 173, 134, and 68 kDa were observed in the specimens of active transmitter. These three protein bands, were absent in the non transmitter.